COMMUNITY POLITICAL PARTICIPATION IN THE ELECTIONS OF HEAD REGION BY THE AGENCY OF NATION AND POLITICAL UNITY IN THE MERAUKE REGENCY - Mulyana Mulyana; Christian Jhonfri Tambunan (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
ABSTRACT. This study aims to analyze the development of community participation in the election of the Regent and Deputy Regent in Merauke Regency from 2015 to 2020 with the efforts made by the National Unity and Politics Agency that has been going well or not as a party from the Regional Government in encouraging community participation. Analysis of these problems used the theory of political participation according to James Roseau. The research method used is descriptive qualitative research method with an inductive approach. The data collection techniques used in the study were interviews and documentation. The steps used in data analysis are data reduction, data verification and drawing conclusions. The author concludes that the development of the political participation of the people of Merauke Regency in the 2015 to 2020 elections has increased by 14.66%, this increase occurs because the people of Merauke Regency have started to have awareness of participating in politics with an active participation style where people tend to participate because of the suffering factor they experience. The style of community participation tends to be direct, subtle, hidden, random and systematic. The author recommends that the National Unity and Politics Agency can conduct socialization to the community using existing mass media such as local radio broadcasts, local television and the use of existing social media. There is a need for cooperation between the National and Political Unity Agency and the KPU, District Government, Village Government, to RT and RW to foster a political culture within the community. Provide guidance and direction to Political Parties as political infrastructure to carry out their functions in society and Supervise and guide the community in conveying aspirations through collaboration with the District Government.